Свойства и сложность задач двухуровневого программирования - Горбачук, В.М.; Шулинок, Г.А. (Теорія оптимальних рішень, 2006)
It is proved that a solution of linear bilevel programming problem is achieved at an extreme point of its constraint region. Based on this property, the algorithm for search a problem solution is suggested. It is demonstrated the mapping of follower’s responses is a polyhedral one. It is showed that in general case a set of problem solutions may not be connected. The NP-completeness of problem is proved.